2018
DOI: 10.1002/elsc.201700018
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and dosing strategies of mineral in anaerobic mono‐digestion of maize straw

Abstract: The influence of the bonding form distribution of Fe, Ni, Co and Mn and their potential bioavailability during the anaerobic degradation of maize straw was investigated. Two reactors were operated over 117 days at 37°C and different dosage strategies of mineral were studied in reactor (R2). Control reactor (R1) was metal‐limited over time. mineral supplementation (1 g L−1) once a week reported the highest methane yield (257 mL g−1 VS) with 30% of increment. Ni and Co predominated in their oxidizable bonding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The effect of the bioavailability of Fe, Ni, Co, and Mn on the CH 4 yield from the AD of MS in the semi-continuous CSTR was studied by González-Suárez [121]. The results indicated a decreasing trend of highly bioavailable fractions of TEs over time.…”
Section: Bioavailability Of Trace Elements (Tes)mentioning
confidence: 99%
“…The effect of the bioavailability of Fe, Ni, Co, and Mn on the CH 4 yield from the AD of MS in the semi-continuous CSTR was studied by González-Suárez [121]. The results indicated a decreasing trend of highly bioavailable fractions of TEs over time.…”
Section: Bioavailability Of Trace Elements (Tes)mentioning
confidence: 99%
“…An unbalanced system might lead to a TE deficiency or a toxic accumulation. González-Suárez et al (2018) observed the TE deficiency in semi-continuous reactors during the digestion of maize straw. The authors operated two SCSTR reactors, a control reactor without metal addition and a reactor with TE supplementation, both with OLR varying from 0.5 to 2.0 gVS L −1 d −1 .…”
Section: Influence Of Reactor Type On Te Supplementationmentioning
confidence: 99%
“…The total concentration of Fe, Ni and Co in the sludge sample was extracted by aqua regia digestion according to [15]. The concentration was measured using atomic absorption spectrometry (AAS, 130B-WFX).…”
Section: Fe Ni and Co Concentrationmentioning
confidence: 99%
“…Extractions were performed in triplicate (1 g wet sludge, based on TS) and the Fe, Ni and Co extracted after SE-step was measured using AAS according to [15]. The result of the analytical determination is provided in mg g -1 TS.…”
Section: Sequential Extractions (Se)mentioning
confidence: 99%
See 1 more Smart Citation